Ancillary mercy [large type] - Leckie, Ann (Leckie, Ann. Imperial Radch series, 2016)
In the stunning conclusion to the trilogy that began with multiple award-winner Ancillary Justice, Breq refuses to flee with her ship and crew and leave the people of Athoek Station in terrible danger. The odds aren't good -- but that's never stopped her before.